Up-regulation of IRF-3 expression through GATA-1 acetylation by histone deacetylase inhibitor in lung adenocarcinoma A549 cells - Wang, Lu-Lu (Oncotarget, 2017)
Interferon regulatory factor 3 (IRF-3) is an important transcription factor for interferon genes. Although its functional activation by viral infection has been widely explicated, the regulatory mechanism of IRF-3 gene expression in cancer cells is poorly understood. In this study, we demonstrated treatment of lung adenocarcinoma A549 cells with trichostatin A (TSA) and valproic acid (VPA), two different classes of histone deacetylase inhibitors, strongly stimulated IRF-3 gene expression. Truncated and mutated IRF-3 promoter indicated that a specific GATA-1 element was responsible for TSA-induced activation of IRF-3 promoter. Chromatin immunoprecipitation and electrophoretic mobility shift assay showed that TSA treatment increased the binding affinity of GATA-1 to IRF-3 promoter. Using immunoprecipitation assay and immunoblotting, we demonstrated that TSA increased the level of acetylated GATA-1 in A549 cells. In summary, our study implied that TSA enhanced IRF-3 gene expression through increased GATA-1 recruitment to IRF-3 promoter and the acetylation level of GATA-1 in lung adenocarcinoma A549 cells.